DsFoxO knockout affects development and fecundity of Drosophila suzukii - Zhao, Shan; Wang, Ruijuan; Liu, Yan; Su, Long; Dai, Xiaoyan; Qin, Dongyun; Chen, Hao; Yin, Zhenjuan; Zheng, Li; Zhai, Yifan (Frontiers in Physiology, 2023)
Forkhead box O (FoxO), a key transcription factor in many species, participates in numerous physiological and pathological processes of organisms through a variety of signaling pathways. In the present study, we established DsFoxO knockout (DsFoxO-KO) strain using CRISPR/Cas9, and the influence on development and fecundity of mutant strain were evaluated. To clarify the corresponding mechanism, a transcriptome analysis was conducted subsequently. The results showed that the survival rates of the DsFoxO-KO strain in larval, pupal, and adult stages were all significantly lower than those of control. The duration of the pupal stage was similar between the two strains; however, durations of egg, larva, adult preoviposition period (APOP), and total APOP (TPOP) in the DsFoxO-KO strain were all significantly longer compared to those of the control strain. The fecundity of the DsFoxO-KO strain was 20.31 eggs/female, which was significantly lower than that of the control strain (430.47 eggs/female). With the transcriptome analysis, 612 differentially expressed genes (DEGs) were identified. Following COG and GO analyses, we found that most of the DEGs were associated with the metabolic process. According to the KEGG database, the mTOR signaling, MAPK signaling, Wnt signaling, and Toll and Imd signaling pathways; insect hormone biosynthesis; autophagy; and apoptosis were altered in the DsFoxO-KO strain. These results demonstrated that knockout of DsFoxO in D. suzukii significantly influenced its development and fecundity, while transcriptome analysis provided insights to explore the corresponding molecular mechanism. These findings highlighted the critical role of FoxO in D. suzukii and might contribute to the development of novel management strategies for these flies in the future.